2015
DOI: 10.1002/dmrr.2570
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of gestational diabetes mellitus among Aboriginal and Torres Strait Islander women in Australia: a systematic review and meta‐analysis

Abstract: The published GDM prevalence among Indigenous women varies markedly, probably due to variation in diagnostic and screening practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 56 publications
0
18
1
Order By: Relevance
“…GDM reported in the present study based in Xiamen was higher compared with previous studies in other cities in China, and Western countries including the USA, Europe and Australia at 9.2, 5.4 and 5.7%, respectively. A meta‐analysis investigating the GDM prevalence in Eastern and Southeast Asia showed the highest prevalence of GDM in Vietnam and Singapore, where approximately one in five mothers was diagnosed GDM, in which study, the incidence of GDM in China was reported to be 11.91%.…”
Section: Discussioncontrasting
confidence: 52%
“…GDM reported in the present study based in Xiamen was higher compared with previous studies in other cities in China, and Western countries including the USA, Europe and Australia at 9.2, 5.4 and 5.7%, respectively. A meta‐analysis investigating the GDM prevalence in Eastern and Southeast Asia showed the highest prevalence of GDM in Vietnam and Singapore, where approximately one in five mothers was diagnosed GDM, in which study, the incidence of GDM in China was reported to be 11.91%.…”
Section: Discussioncontrasting
confidence: 52%
“…However, an increasing prevalence is noted throughout the world [9][10][11]. A high prevalence of GDM is reported in India, with urban (17.8%), semi urban (13.8%) and rural (9.9%) variations based on WHO 1999 criteria [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a report from Spain showed that adopting the IADPSG criteria is associated with increased prevalence and improved pregnancy outcome 15 . However, the prevalence of GDM varies significantly among different ethnic groups [16][17][18][19] , which could result in a different impact on pregnancy outcome. To the best of our knowledge, there is no study of Asians that compared the pregnancy outcomes by using the IADPSG criteria and the C&C criteria.…”
Section: Introductionmentioning
confidence: 99%